Perception and reality in developing an outcome performance measurement system - Wang, Xiao Hu (2002)
This study examines public officials' preferences for different performance measures. Understanding these preferences is important for public officials to reach consensus on performance measurement. It finds that public officials overwhelmingly favor outcome measures, although output measures in addressing organizational goals and achievements. Measurement validity is not a major concern to public officials in their selections of performance measures. Finally, public officials favor the use of outcome measures in performance monitoring rather than in resource allocation. - Reproduced.
Keywords: Performance appraisal